2016
DOI: 10.1016/j.physbeh.2015.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing positive emotional states in dogs using heart rate and heart rate variability

Abstract: A test session consisted of four presentation phases (1 st exposure to stimulus, post exposure, 2 nd exposure, and access to reward). Heart rate (HR) and heart rate variability (HRV) responses were recorded during testing in the experimental room and also when lying resting in a quiet familiar room. A new method of 'stitching' short periods of HRV data together was used in the analysis. When testing different stimuli, no significant differences were observed in HR and LF:HF ratio (relative power in low frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 45 publications
5
72
0
Order By: Relevance
“…In line with previous literature on humans and many other animal species [24,47,63,78,79], the results of this study indicated that mean HR (corrected for dynamic components of behavior) was linked to emotional arousal. Nevertheless, HR provides limited…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with previous literature on humans and many other animal species [24,47,63,78,79], the results of this study indicated that mean HR (corrected for dynamic components of behavior) was linked to emotional arousal. Nevertheless, HR provides limited…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…While the literature on positive emotions in farm animals has grown [5,27,[33][34][35][36][37][38][39][40][41], the same topic has received little attention in companion animals [42][43][44][45][46][47]. Dogs' positive affective states have been investigated in female laboratory beagles tested in four different experimental protocols:…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations